Die Ausstattung kleinerer Häuser in Pompeji (Insula IX 5) Decor-Entscheidungen und ihre Wirkung (62-79 n. Chr.) - Beck, Christian (Decorative Principles in Late Republican and Early Imperial Italy (Decor), 2023)
The book examines the interplay of ancient and new decor elements on Insula IX 5 in Pompeii during the final phase of the city between AD 62-79 . This is the first time that an attempt has been made to grasp the construction and equipment phases of the houses. However, the décor is not only classified chronologically, but analyzed both in terms of the décor decisions made for it and the effect of the décor.